We are not all coping: a cross‐sectional investigation of resilience in the dementia care workforce. (16th October 2015) - Elliott, Kate‐Ellen J.; Stirling, Christine M.; Martin, Angela J.; Robinson, Andrew L.; Scott, Jennifer L.
Abstract: Background: Research on workforce development for high‐quality dementia care more often focuses on enhancing employee knowledge and skill and less on managing employee stress and coping at work. Objective: To review employee stress and coping in response to high job demands in community‐based dementia care organizations in Tasmania, Australia. Methods: Stress and coping in response to job roles of 25 community‐based dementia care workers were reviewed using self‐report questionnaire data. Data were analysed for descriptive results and at an individual case level. Individual participant scores were reviewed for clinically significant stress and coping factors to create worker profiles of adjustment . Results: Two adjustment profiles were found. The 'global resilience' profile, where workers showed positive adjustment and resilience indicating they found their jobs highly rewarding, were very confident in their abilities at work and had a strong match between their personal and organizational values. The second 'isolated distress' profile was only found in a minority and included poor opportunities for job advancement, a missmatch in personal and work values or clinically high levels of psychological distress. Conclusion: Aged care workplaces that advocate employee well‐being and support employees to cope with their work roles may be more likely to retain motivated and committed staff. Future research should consider employee stress and coping at the workforce level, and how this can influence high‐quality care delivery by applying the measures identified for this study. Comparative research across different care settings using meta‐analytic studies may then be possible.